Rancang Bangun Mesin Peniris Minyak Pada Keripik Singkong Secara Otomatis - Arifvhia, Arifvhia; Hendriko, Hendriko; Tianur, Tianur; Rahmawaty, Made (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
The snack business is a very promising business idea in Indonesia because Indonesian people from all walks of life like snacks. The snack food industry is one of the various supporting factors for the Indonesian economy. However, the process of refining oil from food still requires a lot of time. Using an oil-slicing machine on cassava chips automatically will save the use of human labor in the process of closing fried cassava chips to the manual oil separation process. This machine uses the principle of automatic work. With this tool, the oil-draining process becomes very effective. The process of the oil slicing machine on cassava chips automatically starts from the entry of the chips with the movement of the basket actuator from the fryer, then the machine continues to run at once from the process of driving the motor to life, the slicing process, until the spinner actuator stops automatically. The automatic process on this machine uses an AC motor, limit switch, and timer. The test results were very stable on the use of a spinner motor, and the best results were for filling oil for 43 seconds with a heavy load of 3 kg of cassava chips using a timer that had accurate calculations.